수술 전 문맥지결찰이 간절제술 후 잔존간의 재생에 미치는 영향 - 이국종(Kug-Jong Lee); 왕희정(Hee-Jung Wang); 김욱환(Wook-Hwan Kim); 김명욱(Myung-Wook Kim) (Annals of surgical treatment and research, 2005)
Purpose: The goal of this study is to define whether or not preoperative portal vein embolization has any additional role in the total amounts of liver regeneration and functional improvement after major hepatectomy in rat model. In addition, this study is to define obstructive jaundice has any positive or negative effect on it. Methods: There were a total of 650 rats, divided into three experimental groups. Experiment A was done under the normal liver status, experiment B was done under the obstructive jaundice status, experiment C was done under the external biliary drainaged status. Each experimental group was divided into three groups that had been made by different surgery. One was 70% partial hepatectomy, another was 70% portal vein branch ligation, and the other was 70% portal vein ligation followed by 70% hepatectomy. Each operational group required over 60 rats for serial data collection which was taken at the operation and 6, 12, 24, 48, 72 hours after operation. Results: We finally observed that there was no additional regeneration of remaining liver by doing preoperative portal vein embolization. It was same in obstructive jaundice group and external biliary drainaged group. And also, there was no significant fucntional improvement or deterioration by existence of obstructive jaundice. Conclusion: We conclude it is no worth doing preoperative portal vein embolization for getting additional liver regeneration and obstructive jaundice does not has significant positive or negative effect on liver regeneration and hepatic function in itself. KCI Citation Count: 0